2010
DOI: 10.1097/ta.0b013e3181bbd644
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Replantation and Salvage Procedures in Traumatic Ear Amputation

Abstract: Microvascular replantation is the best method for reattaching an amputated ear, giving excellent esthetic results. If only arterial anastomosis is performed, a chemical leech is an option for decompressing the venous congestion. In those patients without a suitable vessel for microanastomosis, nonmicrosurgical methods are suggested, such as a temporoparietal fascia flap, retroauricular pocket procedure, or staged-costal cartilage reconstruction, depending on the ear defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(15 reference statements)
0
16
0
1
Order By: Relevance
“…1 Over the past 30 years, fewer than 40 successful total ear replantations have been reported. 3,14 Successful microvascular reexploration and salvage of a failing ear replant has not been documented in the literature to date. The main technical difficulty with ear replantation is operating in the narrow retroauricular field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Over the past 30 years, fewer than 40 successful total ear replantations have been reported. 3,14 Successful microvascular reexploration and salvage of a failing ear replant has not been documented in the literature to date. The main technical difficulty with ear replantation is operating in the narrow retroauricular field.…”
Section: Discussionmentioning
confidence: 99%
“…These patients, as a group, have notoriously high rates of venous congestion and thrombotic events. 1,2,14,17,18 In digital replantation, the routine use of full heparinization has not been found to be beneficial. 19 However, severe atherosclerotic changes, presence of intimal injury, crush or avulsion, occurrence of intraoperative thrombosis, and surgeon's dissatisfaction with the quality of the anastomoses, despite leaving the zone of injury, continue to be indications for the use of heparin in replantation.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrahim et al [17] presented a single-stage technique of reconstruction in which the cartilage of the avulsed ear is separated from its overlying skin with preservation of the perichondrium, wrapped in a TPF and skin-grafted. Lin et al [18 ] reported on a series of total ear amputations who underwent microsurgical replantation or staged reconstruction procedures with costal cartilage. When partial or complete loss of the ear was encountered after microsurgical replantation, a TPFF draped over the ear cartilage with split-thickness skin graft coverage could be used to salvage the amputated ear in a secondary procedure.…”
Section: Microtia and Traumatic External Ear Amputationmentioning
confidence: 99%
“…Secondary reconstruction of amputated ears is quite difficult to accomplish while maintaining good facial contours. Although various non‐microsurgical methods have been used for reconstruction for amputated ears, they have disadvantages of shape and color mismatch 1, 2, 3. Therefore, microsurgical reattachment should be considered whenever possible.…”
Section: Figurementioning
confidence: 99%